Descontento social en redes de la información por la implementación del proyecto de ley económica y acuerdos con el FMI en el gobierno de Lenin Moreno del año 2019 - Congo Jiménez, Fernando Patricio (2022)
The present research is an investigation that begins by analyzing the reactions to the events that occurred in October 2019 due to the implementation of decree 883, in which the FMI asked the Ecuadorian state, among several measures, to eliminate subsidies such as gasoline on which many depended sectors to generate income, this caused different reactions among the population which were investigated and contrasted in the social network with the highest web traffic, in this case Twitter, which in cases like this, is where the information to the rest of digital platforms comes from it, also contains the chronological order of the most relevant events during the days that said decree was in force, in the contrast of information the press, the population and the opinions of experts, who are the main actors in any social event, intervene, this would help to have of course, not only the situation that society was going through, but also how it was interpreted by her mother. Therefore, in this research a qualitative methodology is used in which there is no participatory intervention with the sources obtained, but it does manage the facts described from these through publications that help to interpret the events hermeneutically, being completely impartial. On October 1, 2019, Ecuador was the protagonist of one of the first massive demonstrations and reactions throughout the country, which would be a point of reference for all of Latin America, but this fact would need to be processed for social understanding, so it was taken into account tells the press that they were the first to issue official government communications, and many were in charge of publishing them with their own opinions that may or may not be well accepted by the population, who are the second group to be considered for the investigation, since many of them are those who directly experienced all the events, thus being able to issue criteria that help to clarify the true intentions of the press, however there is a third group that are the experts, people who, from an objective point of view and in many cases partial to their beliefs they carefully processed and to their interests disseminated information for the understanding of this social event that since From the point of view of the government it was an attempted coup, from the population a claim for rights.